2016
DOI: 10.1111/joic.12325
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcomes and Complications of Intracardiac Echocardiography‐Assisted Patent Foramen Ovale Closure in 1,000 Consecutive Patients

Abstract: ICE-aided closure of PFO using different devices, appeared very safe and effective on very long-term follow up with low incidence of erosion, DT, recurrent ischemic events, MVR new onset or worsening, and permanent AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 31 publications
0
14
0
2
Order By: Relevance
“…Berti et al 13 Pericardial tamponade requiring drainage, stroke/TIA, device embolization requiring surgical removal, major bleeding, and systemic embolism guiding procedures such as atrial septal defect (ASD) or patent foramen ovale occlusions have already been reported by several groups. [20][21][22] With an aging population, not only is the prevalence of atrial fibrillation expected to grow but also is the number of individuals at high risk of bleeding and embolism. Evidence also suggests that with growing operator experience, the results of percutaneous LAAO have steadily improved.…”
Section: Study Definition Of Procedure-related Complicationsmentioning
confidence: 99%
“…Berti et al 13 Pericardial tamponade requiring drainage, stroke/TIA, device embolization requiring surgical removal, major bleeding, and systemic embolism guiding procedures such as atrial septal defect (ASD) or patent foramen ovale occlusions have already been reported by several groups. [20][21][22] With an aging population, not only is the prevalence of atrial fibrillation expected to grow but also is the number of individuals at high risk of bleeding and embolism. Evidence also suggests that with growing operator experience, the results of percutaneous LAAO have steadily improved.…”
Section: Study Definition Of Procedure-related Complicationsmentioning
confidence: 99%
“…No further complications were observed in this patient and no signs of thrombosis were revealed in control TOE in 6‐month follow‐up. Rigatelli et al showed that device thrombosis appeared in 0.5% of 1,000 all‐comer patients after PFO closure with different types of occluders . In a meta‐analysis of 28,142 patients after PFO or ASD closure from 203 studies, Abaci A. et al showed that the risk of device thrombosis in long‐term follow‐up reached 1.2% (95% CI: 1.0–1.4%) .…”
Section: Discussionmentioning
confidence: 99%
“…all-comer patients after PFO closure with different types of occluders [24]. In a meta-analysis of 28,142 patients after PFO or ASD closure from 203 studies, Abaci A. et al showed that the risk of device thrombosis in long-term follow-up reached 1.2% (95% CI: 1.0-1.4%) [25].…”
Section: Discussionmentioning
confidence: 99%
“…The two major shortcomings of ICE are its limited viewing depth and inability to provide three-dimensional volumetric imaging [6]. For this reason (with exception of ASD and patent foramen ovale), there are no large studies to confirm the primary role of ICE in transcatheter procedures in the field of SHD [3, 4, 7]. Another potential issue may be the interference of pacemaker leads with the ICE catheter.…”
Section: Intra-procedural Imaging For Other Transcatheter Shd Proceduresmentioning
confidence: 99%
“…Since atrial septal anatomy can be well defined, ICE has been proven to be very effective in guiding transcatheter closures of an ASD and a patent foramen ovale [6, 7] (Fig. 1).…”
Section: Tee Versus Ice For Transcatheter Closure Of Asdmentioning
confidence: 99%